SIMBOL DAN MAKNA DALAM BUDAYA “MANDIQ LELAYU” SUKU SASAK (KAJIAN SEMIOTIK KULTURAL) - Niswatul Hasanah, Muhammad Hafizin, dan Hadiyaturrido (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2021)
The issues to be studied in this article are the symbols and meanings in the Mandiq Lelayu of Sasak tribe. Mandiq Lelayu culture is one of a series of traditional wedding ceremony Sasak tribe in which contained symbols that contain philosophical meanings. This research is a descriptive qualitative, that is research which try to describe using the words written meaning behind cultural symbols of Mandiq Lelayu. Data collection was done by interview method, and researcher conducted interview with Sasak native at Mamben Lauk Village then continued by record and make a note interview result as advanced method. Data analysis is done by qualitative descriptive, describing the findings in the field with written words based on information directly from informants. Based on preliminary findings the meanings contained in these symbols contain moral values in married life and society.